PEMAHAMAN KONSEP SISWA KELAS XI IPA SMA/MA PADA POKOK BAHASAN SUHU DAN KALOR - Risqa, Moh; Saehana, Sahrul; Darmadi, I Wayan (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to determine, analyze and describe the concept understanding of 11th graders IPA SMA/MA on temperature and heat. This research was a qualitative descriptive study. Respondents examined 21 students who were selected based on the consideration that the class had studied the material of temperature and heat. Analysis of the data through a concept understanding test of 5 questions that were adjusted and validated by expert judgment. The results showed that the proportion of students' overall concept understanding was 54.76%. The percentage of understanding on the first item was 38.09%, the second item was 66.67%, the third item was 63.09%, the fourth item was 50%, and the fifth item was 58.33%. This shows that the understanding of the concepts of 11th grade students in natural science class in high school on temperature and heat was still low. For this reason, it is necessary to pay more attention and remediation on physics topics, especially on the concept of temperature and heat because it affects the other concepts understanding.